Beam forming system modernization at the MMF linac proton injector - Derbilov, V.I.; Esin, S.K.; Nikulin, E.S.; Frolov, O.T.; Yakushev, V.P. (Вопросы атомной науки и техники, 2001)
The isolation improvements of the beam forming system (BFS) of the ММF linac proton injector ion source are reported. The mean beam current and, accordingly, BFS electrode heating were increased when the ММF linac has began to operate regularly in long beam sessions with 50 Hz pulse repetition rate. That is why the BFS electrode high-voltage isolation that was made previously as two consequently and rigidly glued solid cylinder insulators has lost mechanical and electric durability. The substitution of large (160 mm) diameter cylinder insulator for four small diameter (20 mm) tubular rods has improved vacuum conditions in the space of beam forming and has allowed to operate without failures when beam currents being up to 250 mA and extraction and focusing voltage being up to 25 and 40 kV respectively. Moreover, the construction provides the opportunity of electrode axial move. The insulators are free from electrode thermal expansion mechanical efforts in a transverse direction.